Next-generation three-dimensional modelling software for personalized surgery decision-making in perihilar cholangiocarcinoma: multicentre study. Issue 12 (20th September 2021) - Lopez-Lopez, V; Gomez-Perez, B; de Vicente, E; Jiménez-Galanes, S; Mora-Oliver, I; Sabater, L; Huber, T; Lang, H; Brusadin, R; López Conesa, A; Melendez, R; Castro Santiago, M J; et al.
Abstract : Next-generation three-dimensional modelling software for personalized surgery allows spatially accurate depiction of the hepatic and vasculature anatomy based on the complexity and individual variation in each patient, and could facilitate decision-making about preoperative strategy in perihilar cholangiocarcinoma.